Is Irradiated Homologous Costal Cartilage Reliable? A Meta-Analysis of Complication Rates in Rhinoplasty. Issue 3 (August 2022) - Kadakia, Nikita; Nguyen, Cyrus; Motakef, Saba; Hill, Michael; Gupta, Subhas
Background: Irradiated homologous costal cartilage (IHCC) may be a convenient, cost-effective and efficient alternative source of graft material in rhinoplasty; however, a systematic review and meta-analysis on this topic have not been previously performed.Objectives: We sought to summarize and pool data on complications associated with the use of IHCC grafting in rhinoplasty.Methods: A systematic review and meta-analysis was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses criteria. We conducted PubMed, Cochrane, Embase, Web of Science database searches, and screened articles using specific inclusion and exclusion criteria. Pooled complication rates were analyzed using a random-effects model.Results: Of the 13 studies that met criteria for systematic review, 11 studies involving 1017 patients, with 1956 IHCC grafts used, were included in the meta-analysis. Mean follow-up across all studies was 47 months. Overall, the pooled complication rates were 1.14% (95% CI: 0.3%-2.0%) for resorption, 0.5% (95% CI: 0.1%-0.9%) for warping, 1.2% (95% CI: 0.3%-2.1%) for infection, 1.0% (95% CI: 0.1%-2.0%) for mobility, and 0.8% (95% CI: 0.1%-1.6%) for graft removal or replacement. No allergic reactions or systemic disease associated with IHCC use were reported in any of the studies.Conclusions: The overall complications associated with IHCC use in rhinoplasty were very low. Costal cartilage allografts are an area of renewed interest that may represent an alternative to autologous costal cartilage grafting in rhinoplasty due to their low complication rates, convenience, cost-effectiveness, and elimination of donor-site complications.